Upaya Program Peningkatan Keterampilan Deteksi Vitamin C Metode Sederhana Bagi Warga Sekolah Tk Bintang-Bintang Sebagai Upaya Pengendalian Covid-19 - Titin Aryani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Bintang-Bintang Kindergarten is one of the kindergartens located in Argomulyo Village, Sedayu District, Bantul Regency, D.I Yogyakarta. The existence of the COVID-19 Pandemic, forcing all residents of the Bintang-Bintang Kindergarten school to try to prevent COVID-19 infection. Consumption of vitamin C is considered capable of being one way to prevent the transmission of COVID-19. The aim of this service is to conduct training on the simple method of vitamin C detection. This method is sufficient to provide accurate inspection results. It only takes ingredients that are widely available at home. Materials needed such as starch (can be replaced with cornstarch) and iodine (can be replaced with wound medicine such as betadine). Partner's problems are lack of adequate knowledge related to Vitamin C, partner's skills about detecting Vitamin C quickly inadequate, knowledge in distinguishing high and low levels of vitamin C in a food or beverage still needs to be improved, does not yet have adequate facilities for promotion food health related to Vitamin C, for example posters and vitamin C education modules. The solutions offered are education related to vitamin C materials and providing training on Vitamin C detection in a quick and easy method. Outcomes of service are training modules, activity videos, and an increase in knowledge of as many as school partners in vitamin C detection 40.37% as well as increased skills in vitamin C detection.